REBRANDING IDENTITAS VISUAL WISATA PULAU ANGSO DUO KOTA PARIAMAN - Drs. Suib Awrus, M.Pd., Muhamad Ahdanil, Dr. Syafwandi, M.Sn., (Jurusan Seni Rupa FBS UNP Padang, 2018)
The purpose of design, namely to rebranding visual attractions AngsoDuo Island Pariaman city, Featuring a unique and fun impression, able torepresent Branding island tourist attraction that serves to show theidentity of Angso Duo Island. The analytical method chosen in visualrebranding design is SWOT (Strengths, Weakness, Opportunities,Threat). This method is used to find weakness, strength, opportunity andthreat of Angso Duo Island. The result of visual rebranding design ofAngso Duo Island is Brand applied to main media in form of designingmanual and stationery set such as business card, map, cover cd,letterhead, envelope, and notebook as well as supporting media include,t-shirt, totebag, stickers, hats and key chains.Kata kunci: Rebranding, Identitas Visual, Pulau Angso Duo.